Hubungan Antara Kepribadian dengan Engagement Dosen di Institut Ummul Quro Al Islami (Iuqi) Bogor - Abidin, Zainal; Riyad, Muhamad; Ali, Agus; Ramadhan, Muhammad Syahri; Nurfauziah, Zulfa; Hafidz, Abdul; Eliasari, Eliasari; Salam, Rika Putri; Qolbi, Syifaul (STIT Sirojul Falah Bogor, 2022)
Universities are required to have lecturers who are competent and have good performance. The role of the lecturer is crucial to the success of the Vision, Mission and Goals of the Higher Education. Universities expect their lecturers to have better performance, be more process oriented, more involved in leadership, and more capable in knowledge and competence so as to provide added value to the Higher Education which in the end the Higher Education has competitiveness with other universities. Richard S Wellins (2015:525) argues that engagement is when employees enjoy their work, are satisfied with their work conditions, contribute enthusiastically to meet team targets, organizational goals, and there is a sense of belonging to the company, and are committed to the organization. Gibson et al (2006: 113-117) stated that personality is a relatively stable set of characteristics, tendencies, and temperaments (of individuals) that have been formulated by inheritance and by social, cultural, and environmental factors. The results showed that there was a significant relationship between personality and engagement. Based on the results of the research by testing the hypothesis, it is known that the correlation coefficient between personality and engagement (ry1) is 0.995 with the category having a very high/very strong relationship. The probability value is 0.000 < 0.005, then Ho is rejected, so it can be concluded that the correlation coefficient is significant. Thus, this study confirms that there is a significant relationship between personality and engagement. The diversity in engagement related to personality is reflected in the coefficient of determination of 0.990 or 99.0%, while the remaining 1.0% is influenced by other factors. The results of this study get the equation = -13.659 + 1.047 X1 can be used to predict engagement based on personality scores, it can be predicted that every 1 increase in personality score will increase engagement by 1.047 times at a constant -13,659. Keywords: Lecturer Personality, Transformational Leadership, Education Management, Islamic Higher Education, Ministry of Religion, Education Quality.